Biomass, Biofuels, Biochemicals : Recent Advances in Development of Platform Chemicals. - S., Saravanamurugan (Elsevier, 2019)
Biomass, Biofuels, Biochemicals: Recent Advances in Development of Platform Chemicals provides a detailed overview on the experimentally developed methods that facilitate platform chemicals derivation from biomass-based substrates with robust catalyst systems. In addition, the book highlights the green chemistry approach towards platform chemical production. Chapters discuss platform chemicals and global market volumes, the optimization of process schemes and reaction parameters with respect to achieving a high yield of targeted platform chemicals, such as sugars and furonic compounds by modifying the respective catalytic system, the influence of solvents on reaction selectivity and product distribution, and the long-term stability of employed catalysts. Overall, the objectives of the book are to provide the reader with an understanding of the societal importance of platform chemicals, an assessment of the techno-economic viability of biomass valorization processes, catalyst design for a specific reaction, and the design of a catalytic system.